Population Genetic Analysis of the Theileria annulata Parasites Identified Limited Diversity and Multiplicity of Infection in the Vaccine From India - Roy, Sonti; Bhandari, Vasundhra; Barman, Madhumanti; Kumar, Pankaj; Bhanot, Vandna; Arora, Jaspreet Singh; Singh, Satparkash; Sharma, Paresh (Frontiers in Microbiology, 2021)
Background: Apicomplexan parasite Theileria annulata causes significant economic loss to the livestock industry in India and other tropical countries. In India, parasite control is mainly dependent on the live attenuated schizont vaccine and the drug buparvaquone. For effective disease control, it is essential to study the population structure and genetic diversity of the T.annulata field isolates and vaccine currently used in India. Methodology/Results: A total of 125 T.annulata isolates were genotyped using ten microsatellite markers from four states belonging to different geographical locations of India. Limited genetic diversity was observed in the vaccine isolates when compared to the parasites in the field; a level of geographical substructuring was evident in India. The number of genotypes observed per infection was highest in India when compared to other endemic countries, suggesting high transmission intensity and abundance of ticks in the country. A reduced panel of 4 markers can be used for future studies in these for surveillance of the T.annulata parasites in India. Conclusion: High genetic variation between the parasite populations in the country suggests their successful spread in the field and could hamper the disease control programs. Our findings provide the baseline data for the diversity and population structure of T.annulata parasites from India. The low diversity in the vaccine advocates improving the current vaccine, possibly by increasing its heterozygosity. The reduced panel of the markers identified in this study will be helpful in monitoring parasite and its reintroduction after Theileria eradication.